Formation and reductive ring opening reactions of indolyl bicyclic-isoxazolidines-II:7 access to novel natural product analogs. Issue 42 (19th October 2016) - Singh, Gagandeep; Raj, Tilak; Gupta, Vivek; Ishar, Mohan Paul Singh
Graphical abstract: Highlights: Reductive cleavage of indolyl-bicyclic-isoxazolidines (4a –c ) under milder conditions has been attempted. Providing a concise access to α-hydroxy-γ-lactams5a –b . Affording compound6 ; an analog of marine indole alkaloids such as aplysinopsins. Mechanistic rationale of observed reactivity behavior is supported by DFT calculations. Abstract: Attempted reductive cleavage of indolyl-bicyclic-isoxazolidines (4a, b ; R = benzyl, phenyl) with ammonium formate, methanol-THF solvents, at ambient temperature, in the presence of Pd/C lead to facile synthesis of indolyl-α-hydroxy-γ-lactams (5a –b ), derived from reductive cleavage of the NO bond of bicyclic-isoxazolidines, followed by intramolecular recyclization. On the other hand, reaction of4c (R = ethyl) under identical conditions follows a different course affording6, an analogue of naturally occurring marine alkaloid, aplysinopsin. A mechanistic rationale of observed reactivity behavior, supported by DFT calculations, is provided.